Antioxidant effect of curcumin against exposure to malathion in Cyprinus carpio - Mişe Yonar, S.; Yonar, M. E.; Ural, M. Åž. (Cellular and Molecular Biology, 2017)
The aim of this study was to determine protective effects of curcumin on oxidant/antioxidant parameters in Cyprinus carpio exposed to malathion. The fish were exposed to two sublethal concentrations of malathion (0.5 and 1 mg/L), and curcumin (100 mg per kg of fish weight) was simultaneously administered for 14 days. Malondialdehyde level and superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase activities were monitored in liver, kidney and gills, which were collected at the end of the experiment. The results revealed a significant increase in the malondialdehyde levels of the groups that were exposed to malathion. Also, malathion exposure caused a significant increase in superoxide dismutase, catalase, and glutathione-S-transferase activities and a significant decrease in glutathione peroxidase activity. Treatment with curcumin attenuated the malathion-induced oxidative stress by significantly decreasing the levels of malondialdehyde in the tissues. In addition, curcumin reversed the superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase activities. In conclusion, this study demonstrated that malathion caused oxidative stress and negative alterations on the antioxidant enzyme activities of the fish. However, this toxic effect was neutralised by the administration of curcumin.